Leveraging the Critical Decision Method to Develop Simulation-Based Training for Early Recognition of Sepsis. (March 2016) - Patterson, Mary D.; Militello, Laura G.; Bunger, Amy; Taylor, Regina G.; Wheeler, Derek S.; Klein, Gary; Geis, Gary L.
Training hour reductions for resident physicians have resulted in fewer opportunities for novices to manage critically ill patients. Our goals were (a) to understand differences in how novices and experts notice and interpret clinical cues using sepsis as an exemplar and (b) to develop simulations that replicate clinical cues to facilitate acquisition of expertise. Researchers conducted 14 critical decision method (CDM) interviews with four novices (interns), four senior trainees (senior residents), and six faculty (expert) physicians. We interviewed across a spectrum of experience to better assess for experience-based differences in sepsis recognition. Investigators analyzed transcribed interviews using a card sort technique. Experts described more hypothesis testing and violated expectations than novices. Expert–novice differences in sepsis recognition informed the design and future piloting of training scenarios that require novices to seek, interpret, and act on relevant cues.